2017
DOI: 10.1111/dth.12528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of narrow band ultraviolet B phototherapy in the treatment of chronic actinic dermatitis in Chinese patients

Abstract: Few studies have been conducted in chronic actinic dermatitis (CAD) treated with narrowband ultraviolet B (NB UVB) phototherapy, especially in Asian patients. We aim to evaluate the efficacy and safety of NB UVB phototherapy in Chinese patients with CAD. 19 CAD patients of Fitzpatrick skin phototype IV received NB UVB phototherapy in spring and treatments were given 3 times weekly with incremental dose and maintenance therapy was given twice weekly for 3-4 weeks. The mean initial, endpoint, and cumulative dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Management of chronic actinic dermatitis and photo-dermatoses is involved in strict sun protection, photoprotective clothing, UVA, and UVB protective sunscreen (physical or sunscreen) but also includes topical and systemic corticosteroids and PUVA therapy. Narrowband ultraviolet B (NB UVB) phototherapy has shown remarkable therapeutic effects and a safety profile in Chinese patients ( 7 ). Azathioprine, cyclosporine, mycophenolate mofetil, and hydroxyurea are the steroid-sparing agents that have efficacy in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Management of chronic actinic dermatitis and photo-dermatoses is involved in strict sun protection, photoprotective clothing, UVA, and UVB protective sunscreen (physical or sunscreen) but also includes topical and systemic corticosteroids and PUVA therapy. Narrowband ultraviolet B (NB UVB) phototherapy has shown remarkable therapeutic effects and a safety profile in Chinese patients ( 7 ). Azathioprine, cyclosporine, mycophenolate mofetil, and hydroxyurea are the steroid-sparing agents that have efficacy in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Management is centered around strict photoprotection but also includes the use of topical and systemic corticosteroids, TCI, azathioprine, cyclosporine, mycophenolate mofetil, hydroxychloroquine, and PUVA therapy 1 . A report from China showed that narrowband UVB hardening therapy was beneficial in their patients 5 . Our case series indicates that dupilumab may be a viable option for CAD that has proven refractory to standard therapies.…”
Section: Discussionmentioning
confidence: 79%
“…Chronic actinic dermatitis (CAD), synonymous with photosensitive dermatitis and actinic reticuloid syndrome, is a spectrum of diseases with chronic photosensitivity occurring mostly among middle‐aged and older men. It is characterized by eczematous lesions, mainly in sun‐exposed areas 1 . Although the exact mechanism of CAD has not been fully elucidated, the etiology of CAD is generally thought to be a delayed‐type allergy to both endogenous photoallergens and exogenous allergens.…”
Section: Introductionmentioning
confidence: 99%